Rosella (Hibiscus sabdariffa L.) Tea may Protect against Alzheimer’s Disease - Cock, Ian E (Pharmacognosy Communications)
A recent study from a Pohang University, Korea group has reported that the hydroflavone gossypeptin, which is found in relative abundance in Hibiscus sabdariffa L., has therapeutic effects in a 5XFAD Alzheimer’s Disease (AD) mouse model.1 That mouse strain possesses human APP and PSEN1 transgenes, which are linked to familial AD and are known to enhance β-amyloid protein accumulation in brain cells. Mice treated with gossypeptin displayed significantly decreased cognitive impairment similar to those caused by AD.